Assessment of estrogenic, mutagenic and antimutagenic activity of nemorosone - Camargo, Mariana S. [UNESP]; Varela, Soraya D. [UNESP]; Oliveira, Ana Paula S. de [UNESP]; Resende, Flávia Ap. [UNESP]; Cuesta-Rubio, Osmay; Vilegas, Wagner [UNESP]; Varanda, Eliana Aparecida [UNESP] (Sociedade Brasileira de Farmacognosia, 2011)
Currently, a wide range of research involving natural products is focused on the discovery of new drugs in many different therapeutic areas. A great number of the synthetic compounds on the market were derived from natural products, especially plants. Nemorosone is the major constituent of the floral resin of Clusia rosea Jacq., Clusiaceae, and in Cuban propolis. In vitro studies have shown cytotoxic activity in this substance against various tumor cell lines, including those resistant to various cytotoxic drugs, whereas it has low cytotoxicity to non-tumoral cells. Therefore, in order to characterize the biological activity of nemorosone, a substance with potential antitumor activity, and in view of preclinical testing of the toxicity of drug candidate compounds, the main aim of this study was to determine the mutagenic and antimutagenic activity of nemorosone by the Ames test, using the strains TA97a, TA98, TA100 and TA102 of Salmonella typhimurium. Secondly, to characterize the estrogenic activity in an experimental recombinant yeast model (Recombinant Yeast Assay) mutagenic activity was observed at in any of the concentrations in any of the test strains. To evaluate the antimutagenic potential, direct and indirect mutagenic agents were used: 4 nitro-o-phenylenediamine (NPD), mitomycin C (MMC) and aflatoxin B1 (AFL). Nemorosone showed moderate antimutagenic activity (inhibition level 31%), in strain TA100 in the presence of AFL, and strong antimutagenic activity in TA102 against MMC (inhibition level 53%). Estrogenic activity was observed, with an EEq of 0.41±0.16 nM at various tested concentrations.
Keywords: Ames test; antimutagenic activity; estrogenic activity; nemorosone